Project Based Flipped Learning (PjBFL) Model in Increasing Effectiveness Learning : A Systematic Literature Review - Suciati, Ni Nyoman Ayu; Agustini, Ketut; Dantes, Gede Rasben; Sudhata, I Gde Wawan (Universitas Pendidikan Mandalika, 2025)
This study aims to examine the effectiveness of the implementation of PjBFL in improving 21st-century skills and identify interactive media that support its implementation through the Systematic Literature Review (SLR) method. The literature analyzed came from accredited journals indexed in the Scopus and Google Scholar databases, with a publication range of 2020–2024. The search keywords included